Counter-terrorism within the European Union: data surveillance measures - Ponamareva, Veronika (Riga Graduate School of Law, 2018)
The purpose of this thesis is to analyse why Passenger Name Record data has been so strongly and rigoriously criticized by the European Union Data Protection Authorities. In order to reach the aim, European Union legislation on data protection and frameworks related to the Passenger Name Record data use will be assessed. The main focus regarding the frameworks is on the European Union Passenger Name Record Directive, and on the agreements on transfer of such data between the European Union and third countries.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Passenger Name Record Directive; Data protection; European Union